Active surveillance for multidrug-resistant Gram-negative bacteria in the intensive care unit. Issue 6 (October 2015) - Abbott, Iain J.; Jenney, Adam W. J.; Spelman, Denis W.; Pilcher, David V.; Sidjabat, Hanna E.; Richardson, Leisha J.; Paterson, David L.; Peleg, Anton Y.
<x xml:space="preserve">Abstract</x> Summary A short-term program of performing serial active screening cultures (ASC) in the intensive care unit was instituted to establish a method for the detection of antibiotic-resistant Gram-negative bacteria (GNB) and the local rates of colonisation. Of all submitted ASC, 25.9% (30/116 collected swabs) isolated an antibiotic-resistant GNB. ChromID ESBL agar (bioMérieux, France) identified the majority of these organisms, with the additional antibiotic-impregnated media [MacConkey agar (MCA) with ciprofloxacin, MCA with gentamicin and MCA with ceftazidime] adding limited benefit. Compared to swabs performed on admission, 37.8% (14/37) of patients cultured a new antibiotic-resistant isolate on discharge. Serial screening in intensive care has the ability to identify patients with unrecognised colonisation with antibiotic-resistant GNB; however, the increase in the laboratory workload and logistical challenges in the collection of the surveillance swabs may limit this program's expansion.